Mendongkrak Minat Belajar Meraih Prestasi Akademik melalui Pemahaman Law of Attraction - The, Hery Verianto (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
One of aspect of Emotional intelligence is self-awareness. Self-awareness of what you want to achieve and how to achieve is very important for student to learn because it will drive them to achieve academic achievement. Interest needs to be accompanied by a strategy to achieve it. One strategy that is felt need to be introduced to students is the principles of the Law of Attraction. This article shows the principles of the law of attraction that students need to understand and then apply in achieving academic achievement according to their field of interest. This activity begins with identifying knowledge about the law of attraction to students. The next stage is to identify the level of student understanding after the presentation of the material and finally the students' intention to apply the principles of the law of attraction to achieve their academic achievement. The result is that the majority of students understand the material presented as well as the intention to apply the principles of the law of attraction.